Preparation method of superfine alumina-based refractory ceramic material
Patent Information
- Application Number
- CN202611395567.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-09
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]本发明的目的是为了解决现有技术中存在的超细氧化铝残余团聚结构易引起局部差异烧结,并在烧结过程中形成团聚边界串珠状孔裂复合缺陷,影响材料结构均匀性和高温服役稳定性的缺点,而提出的一种超细氧化铝基耐火陶瓷材料的制备方法
[0020] 1. This invention determines the reversal range of differential sintering rates by separately obtaining the sintering shrinkage behavior of agglomerated reference green bodies and matrix reference green bodies. Based on this, the pre-sintering, reversal range crossing, and final densification sintering are controlled in stages. This prevents the ultrafine alumina-based ceramic green body from entering the intense densification process prematurely during the stage when the sintering shrinkage rate of the residual agglomerated region and the outer matrix region changes. This reduces the probability of premature local sintering connection and pore breakage of continuous pores at the agglomerated boundary, and reduces the beaded pore crack composite defects formed along the periphery of the residual agglomerated region.
Smart Images

Figure CN122916634A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of inorganic non-metallic refractory ceramic material preparation technology, and in particular to a method for preparing ultrafine alumina-based refractory ceramic materials. Background Technology
[0002] Alumina-based refractory ceramics possess characteristics such as high temperature resistance, wear resistance, corrosion resistance, and high mechanical strength, and are widely used in high-temperature furnace linings, sintering components, refractory parts, and other high-temperature service applications. With the development of ceramic materials towards higher density, higher strength, and higher reliability, using submicron or finer-grained α-Al₂O₃ powder as the main raw material has become an important way to improve sintering activity and reduce sintering densification temperature. Due to the higher specific surface area and surface energy of fine-grained α-Al₂O₃ powder, the particle diffusion distance is shorter during sintering, making it easier to form sintering necks and promote the densification of the green body. However, fine-grained α-Al₂O₃ powder also has a strong tendency to agglomerate. Residual agglomerates formed during slurry preparation, molding, and drying may be retained inside the ceramic green body, causing differences between the residual agglomerate region and the surrounding matrix region in terms of particle packing state, local pore structure, and sintering kinetics. Conventional techniques typically address these issues by increasing dispersion strength, improving molding density, raising sintering temperature, or extending holding time. However, these methods primarily target the final average density and are insufficient to directly control sintering inhomogeneity caused by localized agglomeration structures.
[0003] During the sintering of alumina-based ceramics, the sintering shrinkage behavior of the residual agglomeration region and the surrounding matrix region does not always maintain the same relationship. As the densification degree of different regions develops, the relative sintering shrinkage rates of the two may undergo phased transitions. In this process, if the agglomeration boundary crack-like pores formed by early differential shrinkage undergo local sintering connections and pore channel breakage before the relative sintering shrinkage rate transition is complete, the continuous boundary pores may be divided into multiple spaced residual pores, forming discontinuous composite defects distributed along the periphery of the original residual agglomeration region together with the local sintering connections and crack-like gaps. These defects may persist even when the material ultimately has a high bulk density and low apparent porosity, forming local weak areas that affect the material's structural uniformity and high-temperature service reliability. Therefore, how to effectively control the temporal relationship between pre-sintering, differential sintering rate transition, and final densification, considering the differential shrinkage and phased changes between the residual agglomeration region and the surrounding matrix region during the sintering process, remains a problem to be solved in the current preparation of ultrafine alumina-based refractory ceramic materials. Summary of the Invention
[0004] The purpose of this invention is to address the shortcomings of existing technologies where residual agglomerates in ultrafine alumina easily cause local differential sintering and form beaded pore cracks at agglomeration boundaries during sintering, affecting the uniformity of the material structure and its high-temperature service stability. Therefore, this invention proposes a method for preparing ultrafine alumina-based refractory ceramic materials.
[0005] To address the problems existing in the prior art, the present invention adopts the following technical solution:
[0006] This invention provides a method for preparing ultrafine alumina-based refractory ceramic materials, comprising the following steps:
[0007] S1. α-Al2O3 powder is added to a liquid dispersion medium for wet dispersion. The resulting alumina slurry is degassed, pressure filtered and shaped, and then dried to obtain an alumina-based ceramic green body.
[0008] S2. Using materials with the same composition and powder source as the α-Al2O3 powder described in step S1, agglomerated reference green bodies and matrix reference green bodies are prepared respectively. Linear shrinkage curves of the agglomerated reference green bodies and matrix reference green bodies are obtained under the same heating conditions. The sintering shrinkage rate of the agglomerated reference green bodies and matrix reference green bodies is determined based on the first-order rate of change of the linear shrinkage curve with respect to temperature. The temperature at which the relationship between the magnitudes of the two sintering shrinkage rates begins to change is determined as the reversal initiation temperature. The temperature at which the magnitude relationship is transformed and the system enters the inverted state is determined as the inversion end temperature. ,by to This constitutes a reversal range for differential sintering rates;
[0009] S3. The alumina-based ceramic green body obtained in step S1 is pre-fired at a higher temperature, and the pre-firing is carried out at a temperature reaching... Completed previously;
[0010] S4. After the pre-firing is completed, continue to raise the temperature so that the alumina-based ceramic green body is transformed from... Continuously increase the temperature to ,exist to No heat preservation stage is set within the differential sintering rate reversal range;
[0011] S5, when the temperature of the alumina-based ceramic preform exceeds The material is then subjected to final densification sintering, followed by cooling to obtain ultrafine alumina-based refractory ceramic material.
[0012] Preferably, in step S1, the volume median particle size D of the α-Al2O3 powder is... 50 No larger than 1.0 μm.
[0013] Preferably, in step S1, the α-Al2O3 powder is added to a liquid dispersion medium, stirred and moistened, and then wet-milled.
[0014] Preferably, in step S2, the agglomerated reference green body is prepared from the same batch of α-Al2O3 powder that retains the particle agglomeration structure, and is used to characterize the sintering shrinkage behavior of the residual agglomerated region in the alumina-based ceramic green body.
[0015] Preferably, in step S2, the matrix reference preform is prepared from the same batch of α-Al2O3 powder that has undergone wet dispersion treatment, and is used to characterize the sintering shrinkage behavior of the matrix surrounding the residual agglomeration region.
[0016] Preferably, in step S2, a thermal expansion meter is used to measure the length of the agglomerated reference green body and the matrix reference green body as a function of temperature, so as to obtain the corresponding linear shrinkage curves.
[0017] Preferably, the pre-firing in step S3 causes the α-Al2O3 powder particles to form an initial sintering neck, and after the initial sintering neck is formed, the temperature continues to rise into the differential sintering rate reversal range.
[0018] Preferably, in step S5, when the temperature exceeds The temperature is then raised to the final sintering temperature, and sintering is performed at the final sintering temperature.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1. This invention determines the reversal range of differential sintering rates by separately obtaining the sintering shrinkage behavior of agglomerated reference green bodies and matrix reference green bodies. Based on this, the pre-sintering, reversal range crossing, and final densification sintering are controlled in stages. This prevents the ultrafine alumina-based ceramic green body from entering the intense densification process prematurely during the stage when the sintering shrinkage rate of the residual agglomerated region and the outer matrix region changes. This reduces the probability of premature local sintering connection and pore breakage of continuous pores at the agglomerated boundary, and reduces the beaded pore crack composite defects formed along the periphery of the residual agglomerated region.
[0021] 2. This invention does not rely on simply increasing the final sintering density as the main control method. Instead, it adjusts the temporal relationship between the reversal of differential sintering rates and the pore clamping, so that the residual agglomerated structure is less likely to be amplified into hidden ring-shaped or shell-shaped defects in subsequent sintering processes. While ensuring the densification of alumina-based refractory ceramic materials, it is beneficial to improve the uniformity of the internal structure of the material, reduce the impact of local defects on the stability of the material, and thus improve its high-temperature service reliability. Attached Figure Description
[0022] The accompanying drawings, which are included to provide a further understanding of the invention and form part of this application, illustrate exemplary embodiments of the invention and, together with their description, serve to explain the invention and do not constitute an undue limitation thereof. In the drawings:
[0023] Figure 1 This is a schematic flowchart of the preparation method of the ultrafine alumina-based refractory ceramic material of the present invention;
[0024] Figure 2 A schematic diagram showing the relationship between the sintering shrinkage rates of the agglomerated reference green body and the matrix reference green body, as well as the reversal range of the differential sintering rates;
[0025] Figure 3 This diagram illustrates the formation of the agglomerated boundary beaded crack ring and the suppression process of this invention. Detailed Implementation
[0026] The technical solution of the present invention will be further described below with reference to the embodiments. The embodiments of the present invention are used to illustrate the preparation process of the present invention, the method for determining the reversal range of differential sintering rates, and the evolution relationship of pore structure at different sintering stages.
[0027] Example 1
[0028] This embodiment uses the volume median particle size D. 50 To prepare ultrafine alumina-based refractory ceramic materials from 0.45 μm α-Al₂O₃ powder, the volume median particle size of the α-Al₂O₃ powder was determined. The particle size was determined using laser particle size analysis.
[0029] like Figure 1 As shown, this invention first wet-disperses α-Al2O3 powder, then degasses the slurry, shapes it, and dries it to obtain an alumina-based ceramic green body. Simultaneously, it determines the reversal range of differential sintering rates by comparing the sintering shrinkage rates of the agglomerated reference green body and the matrix reference green body. ~ ; then in Previously, low-density pre-firing was performed, in ~ The temperature rises continuously across the reversal zone, and... The final densification sintering is then carried out to obtain ultrafine alumina-based refractory ceramic materials.
[0030] S1. Preparation of alumina slurry and molding of alumina-based ceramic green bodies
[0031] Deionized water was used as the liquid phase dispersion medium, and ammonium polyacrylate was used as the dispersant.
[0032] The amount of the active ingredient, ammonium polyacrylate, added is 0.43 wt% of the dry mass of α-Al2O3 powder. An alumina slurry with a solid volume fraction of 50 vol% is prepared based on the actual density of α-Al2O3 powder and the density of deionized water.
[0033] First, add ammonium polyacrylate to deionized water and stir to evenly disperse the ammonium polyacrylate in the deionized water. Then, gradually add α-Al2O3 powder while stirring continuously until all the α-Al2O3 powder has been added and the water has been wetted.
[0034] The resulting slurry was subjected to wet ball milling. High-purity alumina grinding balls were used as the grinding media in the wet ball milling process. The mass ratio of α-Al2O3 powder to high-purity alumina grinding balls was 1:2. The ball milling speed was 85 r / min, and the ball milling time was 6 h.
[0035] After wet ball milling, the alumina slurry is separated from the high-purity alumina grinding balls, and the resulting alumina slurry is subjected to vacuum degassing for 5 minutes.
[0036] The degassed alumina slurry was loaded into a pressure filter molding die and subjected to a 0.4M pressure test. Pressure filtration is performed for 2 hours under pressure, allowing part of the liquid phase in the slurry to be discharged through the porous filtration interface and form a ceramic wet blank.
[0037] After pressure filtration, the ceramic green body is demolded and dried at 60°C for 12 hours to obtain an alumina-based ceramic green body.
[0038] S2. Determination of the reversal range of differential sintering rates
[0039] Using the same batch and same D as S1 50 Agglomerated reference preforms and matrix reference preforms were prepared from α-Al2O3 powder.
[0040] In this embodiment, the residual agglomeration region refers to a localized area within the alumina-based ceramic green body where particle agglomeration remains after the α-Al₂O₃ powder has been wet-dispersed and the green body formed, and where the particle packing state differs identifiable from adjacent areas. The peripheral matrix region refers to the area surrounding the residual agglomeration region where particles are continuously distributed and do not form the same particle cluster boundary characteristics as the residual agglomeration region. The residual agglomeration region and the peripheral matrix region have the same ceramic chemical composition; their differences lie in the particle agglomeration state, local packing state, and pore structure.
[0041] In the agglomeration reference slurry, the addition ratios of α-Al2O3 powder, deionized water, and ammonium polyacrylate, as well as the solid volume fraction, were the same as in S1. However, after all the α-Al2O3 powder was added, mechanical stirring was only performed for 10 minutes, without 6 hours of wet ball milling, in order to retain more particle agglomeration structure.
[0042] The matrix reference slurry was wet-ball milled for 6 hours according to the conditions described in S1.
[0043] Both the agglomerated reference slurry and the matrix reference slurry were subjected to vacuum degassing for 5 minutes, followed by degassing at 0.4 M. Pressure filtration under pressure for 2 hours, followed by demolding and drying at 60°C for 12 hours, yielded agglomerated reference green bodies and matrix reference green bodies, respectively.
[0044] In this embodiment, the agglomerated reference green body is used to obtain the free sintering shrinkage trend corresponding to the residual agglomerated region in the actual alumina-based ceramic green body; the matrix reference green body is used to obtain the free sintering shrinkage trend corresponding to the peripheral matrix region. The two types of reference green bodies are used to compare the differences in sintering kinetics under different particle agglomeration states, and do not mean that the spatial constraint state of the two types of reference green bodies is exactly the same as the corresponding micro-region inside the actual green body.
[0045] To verify the representativeness of the reference green body to the actual micro-region, cross-sectional samples were prepared from the unsintered alumina-based ceramic green body, the agglomerated reference green body, and the matrix reference green body obtained from S1, and observed by scanning electron microscopy.
[0046] In the unsintered alumina-based ceramic green body obtained in S1, the region with identifiable particle cluster boundaries is selected as the residual agglomeration region, and the adjacent region with continuously distributed particles is selected as the outer matrix region.
[0047] Microscopic images were acquired using the same magnification, and the local area porosity was determined using the same image binarization threshold. Ten non-overlapping fields of view were selected for each region, and the results are shown in Table 1.
[0048] Meanwhile, three thermal expansion test specimens were prepared for each type of reference blank.
[0049] The agglomerated reference preform and the matrix reference preform were placed in a thermal expansion apparatus and heated from room temperature to 800°C at a rate of 4°C / min in air atmosphere. The temperature was then held at 800°C for 50 hours and then increased to 1500°C at a rate of 4°C / min.
[0050] During the test, the data on the change of sample length with temperature were continuously recorded, and the length change of each sample was corrected by the blank test results of the thermal expansion instrument.
[0051] Using 5℃ as the data processing interval, points were taken from the corrected linear shrinkage data at equal temperature intervals.
[0052] temperature Linear contraction strain Calculate according to the following formula:
[0053]
[0054] In the formula, For temperature Linear shrinkage strain of the lower reference specimen; The reference length of the specimen before the start of sintering shrinkage analysis; For temperature The length of the lower reference sample.
[0055] temperature Sintering shrinkage rate Calculated using the central difference method:
[0056]
[0057] In this embodiment, the sintering shrinkage rate refers to the rate of change of linear shrinkage strain of the reference green body relative to temperature under a specified heating program, which is used to compare the relative sintering shrinkage change trends of agglomerated reference green bodies and matrix reference green bodies at the same temperature stage; the sintering shrinkage rate referred to in this embodiment refers to the first-order rate of change of linear shrinkage strain with respect to temperature.
[0058] The sintering shrinkage rates of the three agglomerated reference green bodies and the three matrix reference green bodies at each temperature sampling point were calculated, and the corresponding average values and 95% confidence intervals were obtained.
[0059] The average sintering shrinkage rates of agglomerated reference green bodies and matrix reference green bodies were compared along the heating direction. Given that the two types of reference green bodies had already established a stable relationship within consecutive temperature ranges, the temperature corresponding to the first consecutive temperature sampling point when the 95% confidence intervals of the sintering shrinkage rates of the two types of reference green bodies overlapped for the first time within three consecutive temperature sampling points was determined as the reversal initiation temperature. .
[0060] Continue heating until the average sintering shrinkage rates of the two types of reference blanks cross each other, and the 95% confidence intervals of the two types of sintering shrinkage rates are separated again at three consecutive temperature sampling points, while the relationship between the magnitudes of their average sintering shrinkage rates and... Previously, when the process was reversed, the temperature corresponding to the first temperature sampling point that met the above conditions was determined as the reversal end temperature. .
[0061] When there are multiple local intersections in the sintering shrinkage rate curves, only the first complete transformation process that can change the stable sintering shrinkage rate relationship between the two types of reference blanks from the previous stable relationship to the opposite stable relationship is identified as the differential sintering rate reversal process.
[0062] This determines the reversal range of differential sintering rates. :
[0063]
[0064] like Figure 2 As shown, the agglomerated reference green body and the matrix reference green body exhibit different trends in sintering shrinkage rate during the heating and sintering process. With increasing sintering temperature, the sintering shrinkage rates of the two gradually approach and intersect from their original relative values before the reversal, reaching a point at the reversal initiation temperature. Temperature at the end of reversal A reversal zone of differential sintering rates is formed between them; when the temperature exceeds Afterwards, both enter the sintering shrinkage state after reversal, and further enter the final densification stage.
[0065] The reversal of differential sintering rates described in this embodiment refers to a change in the magnitude of the sintering shrinkage rates of the agglomerated reference green body and the matrix reference green body, and does not indicate that the material changes from shrinkage to expansion.
[0066] Table 1. Reference system architecture and differential sintering rate reversal range
[0067] <![CDATA[α-Al₂O₃ powder D 50 / μm]]> 0.45 0.80 Actual residual aggregate region local area porosity / % 34.8±2.2 32.6±2.0 Local area porosity of agglomerated reference preform / % 34.2±2.4 32.1±2.3 Actual local area porosity of the outer matrix region / % 27.1±1.6 25.8±1.5 Local area porosity of matrix reference preform / % 26.7±1.5 25.4±1.7 Reverse starting temperature / ℃ 1285 1315 Reversal End Temperature / ℃ 1325 1360 Previous relationship between sintering shrinkage rate Agglomerated reference green body > Matrix reference green body Agglomerated reference green body > Matrix reference green body The relationship between the sintering shrinkage rate and the subsequent sintering shrinkage rate Agglomerated reference green body < matrix reference green body Agglomerated reference green body < matrix reference green body
[0068] As shown in Table 1, the local area porosity of the actual residual agglomeration region in Example 1 is 34.8%, while that of the agglomerated reference green body is 34.2%. The local area porosity of the actual peripheral matrix region is 27.1%, while that of the matrix reference green body is 26.7%. Combined with microscopic morphological observation, both the agglomerated reference green body and the actual residual agglomeration region have identifiable particle cluster boundaries and corresponding local porosity aggregation characteristics, while both the matrix reference green body and the actual peripheral matrix region exhibit a relatively continuous particle packing structure.
[0069] Therefore, the two types of reference blanks can be used to compare the sintering kinetic trends corresponding to the actual residual agglomeration region and the surrounding matrix region.
[0070] Reversal starting temperature of Example 1 The reversal end temperature is 1285℃. It is 1325℃. Previously, the sintering shrinkage rate of agglomerated reference green bodies was greater than that of matrix reference green bodies; Subsequently, the sintering shrinkage rate of the agglomerated reference green body was less than that of the matrix reference green body, indicating that there is a clear relative sintering shrinkage rate conversion between the two regions with different particle agglomeration states.
[0071] S3 Previous low-density pre-fired
[0072] The alumina-based ceramic preform obtained from S1 was placed in an air atmosphere sintering furnace and heated from room temperature to 800℃ at a heating rate of 4℃ / min, and held at 800℃ for 50h.
[0073] Due to the actual measurement in Example 1 The temperature is 1285℃, therefore 800℃ is lower. .
[0074] In this embodiment, the low densification pre-firing refers to the process at the inversion start temperature. Previous pre-firing treatments caused initial sintering connections and pore structure adjustments between α-Al2O3 particles, but did not aim to achieve the final sintering density. Furthermore, the green body did not enter the final densification stage, characterized by the formation of numerous pores and isolated closed pores, at the end of the pre-firing process.
[0075] To verify the pre-firing state, another accompanying green body prepared under the same conditions as S1 was taken, heated to 800℃ and held for 50h, then the heating was stopped and cooled.
[0076] The apparent porosity, true porosity, and scanning electron microscopy were used to detect the accompanying green body.
[0077] Apparent porosity is denoted as True porosity is denoted as Porosity Calculate according to the following formula:
[0078]
[0079] The specific test results after pre-firing are listed in Table 2.
[0080] Scanning electron microscopy results after pre-firing at 800℃ for 50h showed that the initial sintering neck had appeared at the contact position of adjacent α-Al2O3 particles, while there were still interconnected pore channels around the residual agglomeration area, and no pore structure dominated by isolated closed pores had been formed.
[0081] After the preheating is completed, the temperature is not lowered, and the process directly enters the next heating stage.
[0082] S4, continuously crossing the reversal range of differential sintering rates
[0083] After completing the low-densification pre-firing at 800℃ for 50 hours, the temperature was increased further at 4℃ / min.
[0084] When the temperature reaches That is, after reaching 1285℃, continue to raise the temperature at a rate of 4℃ / min, continuously increasing the temperature from 1285℃ to... That is, 1325℃.
[0085] No heat preservation stage is set between 1285 and 1325℃.
[0086] Through the above sintering process, the green body is continuously heated during the stage when the relative sintering shrinkage rate of the agglomeration reference region and the matrix reference region is switched. This avoids the further growth of the local sintering connection at the agglomeration boundary and the premature breakage of a large number of continuous channels by intermediate heat preservation before the reversal of the differential sintering rate is completed.
[0087] S5 Final densification sintering will then be carried out.
[0088] Once the sintering temperature exceeds 1325℃, continue to increase the temperature to 1500℃ at a rate of 4℃ / min.
[0089] The alumina-based ceramic green body was held at 1500℃ for 2 hours to further shrink and complete the final densification sintering.
[0090] After the heat preservation is completed, heating is stopped and the furnace is cooled to room temperature to obtain ultrafine alumina-based refractory ceramic material.
[0091] To verify the pore structure state in different sintering stages of Example 1, four sets of accompanying green bodies were prepared using the same raw materials, slurry composition, wet ball milling, degassing, pressure filtration and drying conditions as in Example 1.
[0092] After the first batch of accompanying green bodies were pre-fired at 800℃ for 50 hours, sintering was terminated and the green bodies were cooled.
[0093] The second group continues to heat up the billet until... That is, sintering is terminated and cooled after 1285℃;
[0094] The third group of accompanying blanks consists of Continuously increase the temperature to That is, sintering is terminated and cooled after 1325℃;
[0095] The fourth group of accompanying green bodies underwent final densification sintering at 1500℃ for 2 hours in accordance with Example 1.
[0096] The apparent porosity of each group of samples was measured separately. True porosity and according to = - Calculate porosity .
[0097] In this embodiment, the connected pores refer to pores that are connected to adjacent pores or the external open pore network of the sample through continuous channels at the observation scale adopted; the pore interruption refers to the structural evolution process in which the original continuous pore channels are cut off due to local particle contact, sintering neck growth and local densification, so that the original continuous pore channels are divided into two or more discontinuous pore units.
[0098] Polished cross-sections were prepared for each stage of the specimens and observed using scanning electron microscopy. For regions where a single two-dimensional cross-section could not determine whether adjacent pores were connected, continuous cross-section observation and X-ray micro-CT were used for three-dimensional reconstruction.
[0099] In this embodiment, the discontinuous arc-shaped, ring-shaped, or shell-shaped composite defect distributed along the periphery of the identifiable residual agglomeration region and composed of multiple spaced residual holes, local sintered connections between adjacent residual holes, and crack-like slits existing between at least some of the adjacent residual holes is referred to as the agglomeration boundary beaded crack ring.
[0100] The residual pores in the beaded crack ring at the agglomeration boundary can have different sizes, and multiple residual pores are distributed in a discontinuous arc, ring, or shell shape along the periphery of the residual agglomeration region, without the need to form a geometrically complete closed ring.
[0101] like Figure 3 As shown, the continuous channels surrounding the residual agglomeration region can be gradually segmented during differential sintering due to local sintering connections, forming an agglomeration boundary beaded crack ring composed of residual pores, sintered connections, and crack-like gaps; this invention, through... Previously, low-density pre-firing was performed, in ~ The temperature was continuously increased between the intervals of differential sintering rate reversal, and in the process of increasing the temperature between the intervals of differential sintering rate reversal. The final densification sintering is then carried out to keep the agglomeration boundary channels continuous or adjustable before the reversal is completed, thereby reducing the formation of beaded crack rings.
[0102] In specific testing, structures that simultaneously meet the following conditions are identified as agglomerated boundary beaded crack rings:
[0103] (1) The defect is located outside the identifiable residual aggregate region;
[0104] (2) There are at least three mutually spaced residual pores along the periphery of the same residual agglomeration region;
[0105] (3) There is a local sintered connection between adjacent residual holes, or there is a crack-like slit connected to adjacent residual holes;
[0106] (4) Multiple residual pores, sintered joints and crack-like slits form a discontinuous arc-shaped, ring-shaped or shell-shaped distribution with spatial correspondence along the periphery of the residual agglomeration area.
[0107] The porosity test results obtained at different sintering stages are shown in Table 2.
[0108] Table 2. Pore structure detection results at different sintering stages in Example 1
[0109] Preheating at 800℃ for 50 hours 31.8 33.1 1.3 96.1 An initial sintering neck has been formed, the agglomeration boundary channels are continuous, and no obvious beaded crack rings are observed. =1285℃ 18.7 20.6 1.9 90.8 The aggregated boundary crack-like channels still predominate in a continuous morphology. =1325℃ 8.9 11.8 2.9 75.4 The connecting channels are significantly narrowed, with localized sintered connections, but most boundary channels have not yet formed beaded isolated pores. After holding at 1500℃ for 2 hours 0.62 2.51 1.89 24.7 The matrix is highly dense, with a small number of isolated pores and a low number of beaded crack rings detected.
[0110] As shown in Table 2, after pre-firing at 800℃, the apparent porosity of the sample was 31.8%, the true porosity was 33.1%, the closed porosity was only 1.3%, and the proportion of open pores to total pores reached 96.1%, indicating that the green body was still mainly composed of connected open pores at this time.
[0111] Scanning electron microscopy revealed that initial sintering necks had formed between the α-Al₂O₃ particles at this stage, but the channels around the agglomeration region remained continuous. Therefore, pre-firing at 800℃ for 50 hours can form initial particle connections without causing the green body to prematurely enter a stage with a large number of closed pores.
[0112] Heat up to At 1285℃, the apparent porosity decreased to 18.7%, but open pores still accounted for 90.8% of the total pores, and the crack-like channels around the agglomeration area were still mainly continuous structures.
[0113] When the temperature continues to rise to At 1325℃, the apparent porosity decreased to 8.9%, the continuous channels around the agglomeration area became narrower and local sintering connections appeared. However, three-dimensional CT observation showed that most of the agglomeration boundary channels were still not separated to form multiple independent beaded closed pores.
[0114] Therefore, in Example 1, the main differential sintering rate reversal process was completed before the large-scale agglomeration boundary channel pinch-off.
[0115] When the temperature was further increased to 1500℃ and held for 2 hours, the apparent porosity of the sample decreased to 0.62%, indicating that the material had completed sufficient final densification.
[0116] Example 2
[0117] This embodiment uses D 50 Ultrafine alumina-based refractory ceramic materials were prepared from 0.80 μm α-Al2O3 powder.
[0118] Deionized water was used as the liquid phase dispersion medium, and ammonium polyacrylate was used as the dispersant. The amount of effective component of ammonium polyacrylate added was 0.43 wt% of the dry mass of α-Al2O3 powder.
[0119] An alumina slurry with a solid volume fraction of 50 vol% was prepared based on the actual density of α-Al2O3 powder and the density of deionized water.
[0120] Ammonium polyacrylate was added to deionized water and stirred. While stirring continuously, D was gradually added. 50 It is an α-Al2O3 powder with a diameter of 0.80 μm.
[0121] After all the α-Al₂O₃ powder was added and wetted, it was wet-milled using high-purity alumina grinding balls. The mass ratio of α-Al₂O₃ powder to high-purity alumina grinding balls was 1:2, the milling speed was 85 r / min, and the milling time was 6 h.
[0122] After wet ball milling, separate the grinding balls and degas the resulting slurry under vacuum for 5 minutes.
[0123] The deaerated slurry is loaded into a pressure filter molding die and subjected to a pressure filter molding process at 0.4M. Pressure filtration under pressure for 2 hours, followed by demolding, and drying of the resulting wet ceramic blank at 60℃ for 12 hours to obtain an alumina-based ceramic blank.
[0124] Using the same batch of D 50 Agglomerated reference preforms and matrix reference preforms were prepared from 0.80 μm α-Al2O3 powder.
[0125] The raw material composition and solid volume fraction of the agglomeration reference slurry are the same as those of the alumina slurry in this embodiment, but after the α-Al2O3 powder is added, it is only mechanically stirred for 10 minutes and the 6-hour wet ball milling is not carried out.
[0126] The matrix reference slurry was treated with the 6-hour wet ball milling conditions described in this embodiment.
[0127] Both reference slurries were vacuum degassed for 5 minutes at 0.4M. Filter under pressure for 2 hours, then demold and dry at 60℃ for 12 hours.
[0128] Three agglomerated reference samples and three matrix reference samples were prepared respectively, and thermal expansion and sintering shrinkage tests were performed according to the same method described in Example 1.
[0129] As can be seen from Table 1, the reversal initiation temperature in this embodiment is... The reversal end temperature is 1315℃. It is 1360℃.
[0130] Previously, the sintering shrinkage rate of agglomerated reference green bodies was greater than that of matrix reference green bodies; Subsequently, the sintering shrinkage rate of the agglomerated reference green body is less than that of the matrix reference green body.
[0131] This embodiment does not use the method of Embodiment 1. and As the boundary of the sintering stage, and using D 50 The measured values for 0.80 μm α-Al2O3 powder were obtained. and .
[0132] The alumina-based ceramic green body obtained in this embodiment was placed in an air atmosphere sintering furnace and heated to 800°C at a rate of 4°C / min, and held at 800°C for 50 hours.
[0133] Because 800°C is lower than that of this embodiment. =1315℃, therefore this pre-firing occurs before the start of the differential sintering rate reversal.
[0134] After preheating at 800℃ for 50 hours, the temperature is not lowered, but continues to rise at 4℃ / min.
[0135] When the sintering temperature reaches 1315℃, continue to raise the temperature to 1360℃ at a rate of 4℃ / min, and do not set a holding stage between 1315℃ and 1360℃.
[0136] After the temperature exceeds 1360℃, continue to raise the temperature to 1550℃ and keep it at 1550℃ for 2 hours.
[0137] After the heat preservation is completed, the material is cooled to room temperature in the furnace to obtain ultrafine alumina-based refractory ceramic material.
[0138] The final test results of the obtained materials are listed in Table 3.
[0139] Comparative Example 1
[0140] This comparative example uses D. 50 It is an α-Al2O3 powder with a diameter of 0.45 μm.
[0141] Deionized water was used as the liquid phase dispersion medium, and ammonium polyacrylate was used as the dispersant. The amount of effective component of ammonium polyacrylate added was 0.43 wt% of the dry mass of α-Al2O3 powder, and the solid volume fraction of alumina slurry was 50 vol.
[0142] Ammonium polyacrylate was added to deionized water and stirred, and then α-Al2O3 powder was gradually added.
[0143] After the powder was completely wetted, it was wet ball milled using high-purity alumina grinding balls. The mass ratio of α-Al2O3 powder to high-purity alumina grinding balls was 1:2, the ball milling speed was 85 r / min, and the ball milling time was 6 h.
[0144] After wet ball milling, separate the grinding balls and degas the resulting slurry under vacuum for 5 minutes.
[0145] The deaerated slurry was heated to 0.4M Pressure filtration was performed under pressure for 2 hours, followed by demolding and drying at 60°C for 12 hours to obtain an alumina-based ceramic green body.
[0146] This comparative example uses the same batch of α-Al₂O₃ powder as Example 1, therefore the corresponding reversal initiation temperature is... The reversal end temperature is 1285℃. It is 1325℃.
[0147] Unlike Example 1, this comparative example does not undergo low-densification pre-firing at 800°C for 50 hours.
[0148] The dried alumina-based ceramic blank was placed directly in an air atmosphere sintering furnace and heated continuously from room temperature to 1500℃ at a rate of 4℃ / min, and held at 1500℃ for 2 hours.
[0149] After the heat preservation period, the furnace is cooled to room temperature.
[0150] The obtained material was tested for bulk density, apparent porosity, true porosity, closed porosity, and agglomeration boundary beaded crack ring.
[0151] Scanning electron microscopy and X-ray micro-CT observations showed that, due to the lack of low-densification pre-firing at 800℃, the local pore size difference between the original agglomeration area and the surrounding matrix was not sufficiently adjusted before entering the rapid shrinkage stage. During the subsequent sintering process, some agglomeration boundary continuous channels showed local sintering connection and truncation earlier.
[0152] In the final sample, multiple residual pores were observed to be arranged at intervals along the periphery of the original agglomeration area, and separated from each other by local sintered joints and crack-like slits, which met the identification criteria of beaded crack rings at the agglomeration boundary.
[0153] Comparative Example 2
[0154] This comparative example uses D. 50 It is an α-Al2O3 powder with a diameter of 0.45 μm.
[0155] Deionized water was used as the liquid phase dispersion medium, and ammonium polyacrylate was used as the dispersant. The amount of effective component of ammonium polyacrylate added was 0.43 wt% of the dry mass of α-Al2O3 powder, and the solid volume fraction of alumina slurry was 50 vol.
[0156] First, add ammonium polyacrylate to deionized water and stir, then gradually add α-Al2O3 powder.
[0157] After the powder is completely wetted, wet ball milling is performed using high-purity alumina grinding balls. The mass ratio of α-Al2O3 powder to high-purity alumina grinding balls is 1:2, the ball milling speed is 85 r / min, and the ball milling time is 6 h.
[0158] After wet ball milling, separate the grinding balls and degas the resulting slurry under vacuum for 5 minutes.
[0159] The deaerated slurry was heated to 0.4M Pressure filtration was performed under pressure for 2 hours, followed by demolding and drying at 60°C for 12 hours to obtain an alumina-based ceramic green body.
[0160] The obtained alumina-based ceramic green body was placed in an air atmosphere sintering furnace and heated to 800℃ at a rate of 4℃ / min, and held at 800℃ for 50h.
[0161] After preheating is complete, do not cool down, but continue to heat up at 4℃ / min.
[0162] Since this comparative example uses the same batch of α-Al₂O₃ powder as Example 1, its It is 1285℃. It is 1325℃.
[0163] exist and Determine the intermediate temperature :
[0164]
[0165] Therefore, we can conclude that:
[0166]
[0167] When the billet is heated to 1305℃, it is held at 1305℃ for 1 hour.
[0168] After the heat preservation period, continue to increase the temperature to 1500℃ at a rate of 4℃ / min, and maintain the temperature at 1500℃ for 2 hours.
[0169] After the heat preservation period, the furnace is cooled to room temperature.
[0170] Scanning electron microscopy and X-ray micro-CT observations showed that during the heat treatment at 1305℃, the local sintering connection of the agglomeration boundary pores increased significantly, and some of the original continuous crack-like pores were pinched off before the differential sintering rate reversal was completed.
[0171] After final sintering, a discontinuous arc-shaped or ring-shaped defect structure is formed around some residual agglomeration areas, consisting of multiple residual pores, locally sintered joints, and crack-like slits.
[0172] Final structural testing of the examples and comparative examples
[0173] Three parallel final sintering samples were prepared for each of Example 1, Example 2, Comparative Example 1 and Comparative Example 2.
[0174] Bulk density, apparent porosity, and true porosity were measured using the same method, while closed porosity was measured. according to = - calculate.
[0175] For the beaded crack ring at the agglomeration boundary, 10 observation areas that could clearly identify the residual agglomeration region were selected for each parallel sample using a scanning electron microscope, and a total of 30 residual agglomeration regions were counted for each group.
[0176] The total number of residual agglomeration areas actually included in the statistics for each group is denoted as . The number of residual agglomerated regions with beaded crack rings at agglomerated boundaries is denoted as . .
[0177] Detection rate of clustered boundary beaded crack ring Calculate according to the following formula:
[0178]
[0179] The test results of each embodiment and comparative example are shown in Table 3.
[0180] Table 3 Final sintering results of the examples and comparative examples
[0181] <![CDATA[D 50 / μm]]> 0.45 0.80 0.45 0.45 / ℃ 1285 1315 1285 1285 / ℃ 1325 1360 1325 1325 Final sintering conditions 1500 ℃×2 h 1550 ℃×2 h 1500 ℃×2 h 1500 ℃×2 h Bulk density after firing / (g·cm⁻³) 3.88 3.85 3.86 3.90 Apparent porosity / % 0.62 0.94 0.81 0.45 True porosity / % 2.51 3.27 3.02 2.01 Porosity / % 1.89 2.33 2.21 1.56 Number of residual agglomeration areas included in the statistics 30 30 30 30 Number of beaded crack ring regions 2 4 13 11 Detection rate of beaded crack rings / % 6.7 13.3 43.3 36.7
[0182] As shown in Table 3, the final calcined bulk densities of Example 1, Comparative Example 1, and Comparative Example 2 are 3.88 g / cm³, 3.86 g / cm³, and 3.90 g / cm³, respectively, and the three are within a similar range of final density.
[0183] Among them, the bulk density of Comparative Example 2 was even slightly higher than that of Example 1, but the detection rate of agglomeration boundary beaded crack rings in Comparative Example 2 still reached 36.7%, which was significantly higher than 6.7% in Example 1.
[0184] Therefore, the reduction in the beaded crack ring at the agglomeration boundary cannot be simply attributed to the increase in final bulk density.
[0185] In Example 1, in Previously, a low-densification pre-sintering process was performed at 800℃ for 50 hours to form initial sintering necks between α-Al2O3 particles, while retaining a pore structure dominated by open, interconnected pores. The temperature was then continuously increased within the differential sintering rate reversal range of 1285–1325℃ without a holding stage, and... Then, final densification sintering will be carried out.
[0186] In the final embodiment 1, beaded crack rings at the agglomeration boundary were observed in only 2 out of 30 residual agglomeration regions, with a detection rate of 6.7%.
[0187] Comparative Example 1: After removing the low-densification pre-burning, 13 out of 30 residual agglomeration areas showed beaded crack rings at the agglomeration boundary, with a detection rate of 43.3%.
[0188] This indicates that if the particle contact and pore structure are not pre-adjusted before entering the significant differential sintering stage, the residual agglomeration structure is more likely to be amplified into agglomeration boundary composite defects during the subsequent differential sintering process.
[0189] Although Comparative Example 2 retained the 800℃, 50h low-densification pre-fired condition, it also... to Set the temperature between 1305℃ and maintain it for 1 hour.
[0190] Its final bulk density reached 3.90 g / cm³, which is a three-dimensional density. 50 The highest concentration was found in samples with a particle size of 0.45 μm, but beaded crack rings were still observed in 11 of the 30 residual agglomeration regions, with a detection rate of 36.7%.
[0191] The above results indicate that promoting local densification before the differential sintering rate reversal is completed can improve the macroscopic densification, but it will cause the continuous pores at the agglomeration boundary to form local sintering connections and pore clamping in advance while the relative shrinkage rate is still in the process of conversion, so that multiple residual pores are fixed along the periphery of the original agglomeration area.
[0192] Example 2 uses D 50 The α-Al₂O₃ powder is 0.80 μm in size, and its actual measurement... 1315℃ The temperature is 1360℃. After redetermining the differential sintering rate reversal range according to the method of this invention, in Previously, low-density pre-firing was carried out, in to Continuous heating and between After the final sintering was completed, the detection rate of agglomeration boundary beaded crack rings was 13.3%, which was still significantly lower than that of Comparative Example 1 and Comparative Example 2, which used a timing control method other than that of this invention.
[0193] As can be determined from Examples 1, 2, Comparative Example 1 and Comparative Example 2, the reversal temperatures of the different sintering rates corresponding to α-Al2O3 powders with different particle sizes are not exactly the same. Therefore, it is not appropriate to divide the sintering stages of the entire alumina powder system by a uniform fixed temperature.
[0194] This invention obtains sintering shrinkage rate curves for agglomerated reference green bodies and matrix reference green bodies for actual α-Al2O3 powder and molding state, respectively, and determines the sintering shrinkage rate based on these curves. and This allows the three stages of pre-firing, differential sintering rate reversal, and final densification to correspond to the actual powder sintering kinetics.
[0195] Based on the test results in Tables 1-3, it can be seen that the residual agglomerated region in the actual alumina-based ceramic green body differs from the surrounding matrix region in terms of local particle packing state and pore structure. The agglomerated reference green body and the matrix reference green body can respectively reflect the shrinkage behavior changes of the above two types of regions during the heating and sintering process. The sintering shrinkage rate of the two types of reference green bodies shows a relative shift with increasing temperature. Among them, the reversal initiation temperature measured in Example 1... 1285℃, the temperature at which the reversal ends. The temperature was 1325℃, as measured in Example 2. 1315℃ The temperature was 1360℃, indicating that there is an identifiable reversal range of sintering rate under different particle size conditions.
[0196] In Example 1, after pre-firing at 800℃ for 50 hours, initial sintering necks had formed between the α-Al₂O₃ particles, while the proportion of open pores to total pores remained at 96.1%, indicating that large-scale pore closure had not yet occurred at this stage, and the internal pores of the green body remained largely interconnected. In subsequent... Continuously increase the temperature to During the process, the crack-like channels around the residual agglomeration area remain continuous or have room for further adjustment. After the differential sintering rate is reversed, the final densification sintering stage is entered.
[0197] The final sintering results show that, under similar bulk density conditions, the detection rate of agglomeration boundary beaded crack rings in Example 1 was 6.7%, while in Comparative Example 1 (where low-density pre-sintering was omitted), it was 43.3%. ~ Comparative Example 2, which included a holding stage within the differential sintering rate reversal range, showed a failure rate of 36.7%. These results indicate that solely focusing on increasing the final densification level as the sintering control objective is insufficient to effectively suppress the formation of beaded porosity composite defects at the residual agglomeration boundaries. Furthermore, the timing sequence between the pre-sintering stage, the differential sintering rate reversal stage, and the final densification stage significantly influences the formation of these defects.
[0198] Based on the pore structure and sintering shrinkage behavior at each stage, it can be concluded that the residual agglomerate structure of ultrafine α-Al2O3 powder after molding has different local sintering kinetic characteristics from its surrounding matrix, and the relative sintering shrinkage rate can change during the heating process. When the continuous channels at the agglomeration boundary undergo strong local sintering connection and channel breakage before the reversal of the differential sintering rate is completed, the original continuous boundary channels are easily separated into multiple residual pores, which, together with the local sintering connection and crack-like gaps, form a discontinuously distributed agglomeration boundary beaded crack ring along the periphery of the residual agglomeration region.
[0199] This invention, through Previously, low-densification pre-sintering was implemented to form initial sintering necks between particles, preventing premature and large-scale closure of agglomeration boundary channels. Subsequently, the temperature was continuously increased between #imgpt137# and #imgpt138#, traversing the differential sintering rate reversal zone, without setting a holding stage in this zone, and final densification sintering was carried out after the temperature exceeded #imgpt139#. This ensures that the differential sintering rate conversion between the residual agglomeration region and the surrounding matrix is completed before the large-scale pinching of agglomeration boundary channels occurs, reducing the possibility of premature segmentation and solidification of continuous boundary channels into beaded pore crack composite defects.
[0200] The test results of the examples and comparative examples show that the inhibitory effect of the present invention on the beaded crack ring at the agglomeration boundary does not simply rely on increasing the final bulk density of the alumina-based refractory ceramic material. Instead, it achieves the regulation of the agglomeration boundary defect formation process by coordinating the relative timing between the differential sintering kinetics conversion process between the residual agglomeration region and the outer matrix and the agglomeration boundary channel pinch-off process, thereby improving the uniformity of the microstructure of the sintered material.
[0201] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for preparing an ultrafine alumina-based refractory ceramic material, characterized in that, Includes the following steps: S1. α-Al2O3 powder is added to a liquid dispersion medium for wet dispersion. The resulting alumina slurry is degassed, pressure filtered and shaped, and then dried to obtain an alumina-based ceramic green body. S2. Using materials with the same composition and powder source as the α-Al2O3 powder described in step S1, agglomerated reference green bodies and matrix reference green bodies are prepared respectively. Linear shrinkage curves of the agglomerated reference green bodies and matrix reference green bodies are obtained under the same heating conditions. The sintering shrinkage rate of the agglomerated reference green bodies and matrix reference green bodies is determined based on the first-order rate of change of the linear shrinkage curve with respect to temperature. The temperature at which the relationship between the magnitudes of the two sintering shrinkage rates begins to change is determined as the reversal initiation temperature. The temperature at which the magnitude relationship is transformed and the system enters the inverted state is determined as the inversion end temperature. ,by to This constitutes a reversal range for differential sintering rates; S3. The alumina-based ceramic green body obtained in step S1 is pre-fired at a higher temperature, and the pre-firing is carried out at a temperature reaching... Completed previously; S4. After the pre-firing is completed, continue to raise the temperature so that the alumina-based ceramic green body is transformed from... Continuously increase the temperature to ,exist to No heat preservation stage is set within the differential sintering rate reversal range; S5, when the temperature of the alumina-based ceramic preform exceeds The material is then subjected to final densification sintering, followed by cooling to obtain ultrafine alumina-based refractory ceramic material.
2. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 1, characterized in that, In step S1, the volume median particle size D of the α-Al2O3 powder is... 50 No larger than 1.0 μm.
3. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 1 or 2, characterized in that, In step S1, the α-Al2O3 powder is added to a liquid dispersion medium, stirred and moistened, and then wet-milled.
4. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 1 or 2, characterized in that, In step S2, the agglomerated reference green body is prepared from the same batch of α-Al2O3 powder that retains the particle agglomeration structure, and is used to characterize the sintering shrinkage behavior of the residual agglomerated region in the alumina-based ceramic green body.
5. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 4, characterized in that, In step S2, the reference substrate is prepared from the same batch of α-Al2O3 powder that has undergone wet dispersion treatment, and is used to characterize the sintering shrinkage behavior of the substrate surrounding the residual agglomeration region.
6. The method for preparing ultrafine alumina-based refractory ceramic materials according to claim 1, 4, or 5, characterized in that, In step S2, a thermal expansion meter is used to measure the length of the agglomerated reference green body and the matrix reference green body as a function of temperature, so as to obtain the corresponding linear shrinkage curves.
7. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 1, characterized in that, The pre-firing in step S3 causes the α-Al2O3 powder particles to form an initial sintering neck, and after the initial sintering neck is formed, the temperature continues to rise into the differential sintering rate reversal zone.
8. The method for preparing ultrafine alumina-based refractory ceramic material according to claim 1, characterized in that, In step S5, when the temperature exceeds The temperature is then raised to the final sintering temperature, and sintering is performed at the final sintering temperature.